Inhibitor development and mortality in non‐severe hemophilia A. (10th June 2015) - Eckhardt, C. L.; Loomans, J. I.; van Velzen, A. S.; Peters, M.; Mauser‐Bunschoten, E. P.; Schwaab, R.; Mazzucconi, M. G.; Tagliaferri, A.; Siegmund, B.; Reitter‐Pfoertner, S. E.; van der Bom, J. G.; Fijnvandraat, K.; et al.
Summary Background The life expectancy of non‐severe hemophilia A (HA) patients equals the life expectancy of the non‐hemophilic population. However, data on the effect of inhibitor development on mortality and on hemophilia‐related causes of death are scarce. The development of neutralizing factor VIII antibodies in non‐severe HA patients may dramatically change their clinical outcome due to severe bleeding complications. Objectives We assessed the association between the occurrence of inhibitors and mortality in patients with non‐severe HA. Methods In this retrospective cohort study, clinical data and vital status were collected for 2709 non‐severe HA patients (107 with inhibitors) who were treated between 1980 and 2011 in 34 European and Australian centers. Mortality rates for patients with and without inhibitors were compared. Results During 64 200 patient‐years of follow‐up, 148 patients died (mortality rate, 2.30 per 1000 person‐years; 95% confidence interval (CI), 1.96–2.70) at a median age of 64 years (interquartile range [IQR], 49–76). In 62 patients (42%) the cause of death was hemophilia related. Sixteen inhibitor patients died at a median age of 71 years (IQR, 60–81). In ten patients the inhibitor was present at time of death; seven of them died of severe bleeding complications. The all‐cause mortality rate in inhibitor patients was > 5 times increased compared with that for those without inhibitors (age‐adjusted mortality rate ratio, 5.6). Conclusion Inhibitor development in non‐severe hemophilia is associated with increased mortality. High rates of hemophilia‐related mortality in this study indicate that non‐severe hemophilia is not mild at all and stress the importance of close follow‐up for these patients.